Financial credibility, ownership, and financing constraints in private firms - Hope, Ole-Kristian; Thomas, Wayne; Vyas, Dushyantkumar (Journal of International Business Studies, 2011)
As shown in the international business literature, the ability of controlling owners to extract private benefits is greater in countries with weaker legal institutions. In these countries, providing credible financial information could play an especially important role in reducing information asymmetry between private firms and external providers of finance. For our sample of firms across 68 countries, we find that firms with greater financial reporting credibility (i.e., annual financial statements reviewed by an external auditor) experience significantly lower perceived problems in gaining access to external finance. Further, the impact of financial credibility in reducing financing constraints in the presence of a controlling owner is more pronounced in countries with weaker creditor rights. Given the predominance of private firms around the world, their economic significance, and the fact that an increasing number of private firms now operate in multinational environments with different institutional features, we contribute to the literature on the role of financial information, firm characteristics, and country-level institutions for an important and interesting group of firms.